The dark side of technological innovation - Ran, Bing (Contemporary perspectives on technological innovation, management, and policy., 2013)
Managing technological innovations and related policy and strategy issues have been a central focus of the new millennium. This book series presents an interdisciplinary scholarship and dialogue on the management of innovation and technological change in a global context from a variety of perspectives, including strategic, managerial, behavioral, and policy issues. Papers selected in this volume have four prominent themes: the wide spread interests and the global application of the technological innovation; the practicality of the research on technological innovation implementation to foster success and financial growth; the socio-technical challenges behind innovation and creativity that might outweigh the benefits; and the new principles/practices/perspectives on our understanding of the technological innovation. Contributed by prominent scholars and practitioners from around the world in innovation, management and policy area, this book will become a very useful read for anyone who is interested in learning the most contemporary perspectives on the subject.